Reingeniería de los Procesos de Inducción y Evaluación del desempeño en Laboratorios Bagó del Ecuador en el período 2014. - Osejos Naranjo, María Janeth (2014)
The work “Reengineering process of Induction and Performance Evaluation of Laboratories Bagó of Ecuador”, it´s main objective was to review and establish a process of induction on the Performance Evaluation for its correct use and provide aligned tools to the competencies defined for sales team. Exploratory and confirmatory analytical: To meet this objective research methods were used. As tools for obtaining information interview, surveys, analysis of existing processes and formats used for performance evaluation were used. It was concluded as a result of this investigation and as a necessity Area Commercial, have an induction process on the skills and behaviors described for each position and are considered in the performance evaluation and the methodology , frequency and manner formats to use for this activity, revealing that evaluators and evaluated. To meet these needs training workshops “Performance Evaluation " organized and evaluation forms adjusted to the skills and behaviors of office were changed.